The sleeping bread - Czernecki, Stefan; Rhodes, Timothy (Hyperion Paperbacks for Children, 1993)
The bitter tear of an unwanted beggar causes the bread dough in the bakery shop to "sleep" and the villagers fear it will not rise in time for the festival of the town's patron saint
Keywords: Bread / Juvenile fiction; Beggars / Juvenile fiction; Bakers and bakeries / Fiction; Beggars; Bread; Humanität; Bettler; Nächstenliebe; Bäcker; Guatemala / Juvenile fiction; Guatemala; Bilderbuch